Identification of cold-tolerant breeding lines by quantitative trait loci associated with cold tolerance in rice - Jena, K.K.; Kim, S.M.; Suh, J.P.; Yang, C.I.; Kim, Y.G. (Wiley, 2012)
Low temperature or cold stress is one of the major abiotic stresses limiting rice (Oryza sativa L.) production and productivity in the temperate rice growing regions as well as in tropical high lands worldwide. Low temperature at the reproductive stage causes high sterility and decreases production. In this study, we assessed recombinant inbred lines (RILs) that possessed cold‐tolerance genes and/or quantitative trait loci (QTL) from the donor line IR66160‐121‐4‐4‐2 in the genetic background of a cold‐sensitive japonica cultivar, Geumobyeo. The selected 15 RILs with QTL for cold tolerance were phenotyped for three main agronomic traits—culm length (CL), days to heading (DTH), and spikelet fertility (SF)—which were most affected during cold stress. The RILs with cold‐tolerant and cold‐sensitive parents were evaluated under cold‐water (18–19°C) irrigation in the field and cold‐air temperature (17–18°C) in the temperature‐controlled greenhouse. The RILs showed significant differences in these traits compared to the cold‐sensitive parent. Traits CL and DTH exhibited positive correlation with SF in the selected breeding lines. The SF of the selected breeding lines was higher (51–81%) than that of the cold‐sensitive parent, Geumobyeo (7%). Our results confirmed that cold tolerance was associated with SF but the traits CL and DTH were differently associated with cold tolerance. The cold‐tolerant breeding lines selected in this study had at least one of the three QTL associated with cold tolerance. The breeding lines confirmed to have cold tolerance are useful to breed cold‐tolerant cultivars and increase our understanding of the mechanism of cold tolerance in rice.